Cognitive Distortions And It’s Relationship With Exam Anxiety And The Perceived Self-Efficacy Among Secondary School Students In Sakhnin City - Knamh, Hussin Kmal Hussin; Nsrawen, Moeen (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the cognitive distortions and It’s relationship with exam anxiety and the perceived self-efficacy among secondary school students in sakhnin city in palestine. The study sample consisted of (175) male and female of students in the secondary stage in sakhnin city during the second semester of the academic year (2018/2019). To achieve the aim of the study, the researcher developed the standards of both cognitive distortions, and anxiety of the exam, and perceived self-efficacy. Validity and reliability for both scales were obtained.The results showed a low level of cognitive distortions and exam anxiety among secondary school students in sakhnin city, and a high level of perceived self-efficacy among secondary school students in sakhnin city. The results showed a statistically significant positive correlation between cognitive distortions and exam anxiety among secondary school students in sakhnin city. Also a statistically significant negative correlation found between cognitive distortions and perceived self-efficacy among secondary school students in sakhnin city.Several recommendations and suggestions were provided; including the need for future research investigating the relationships between the cognitive distortions, and anxiety of the exam, and perceived self-efficacy in the light of gender and classroom variables.
Keywords: Cognitive Distortions; Exam Anxiety; Perceived Self-Efficacy; Secondary School Students; Sakhnin City